Enhancing Netizen As A Digital Marketing Activity Toward Strategic Branding: A Case Study of â€œXYZâ€ Brand - Hidayat, Nila Krisnawati; Tobing, Rudy (Journal the Winners: Economics, Business, Management, and Information System Journal, 2012)
This study is focused on the role of netizen in digital marketing activities to attempt the development of strategic brand of â€œXYZâ€. The purpose of this study to identify whether netizen as users have recognize the â€œXYZâ€ brand as a product of internet mobile, through four variables of brand performances: delivery message, creative advertisement, product understanding, and brand association. It is also to measure usersâ€™ level of awareness to the website of â€œmurah itu XYZâ€. The research methodology applied in this study is descriptive quantitative study Â using Likert scale. The result shows that the highest level of brand performance is not only from delivery message, but it also indicates that netizen have recognized the â€œXYZâ€ as internet mobile under the activity of digital marketing. In addition, users are not aware yet to the website of â€œmurah itu XYZâ€. The content of the mobile advertising should be increased in the near future.